An overview of utilizing short video on social media platform as T&L tool during ODL: case study of diploma civil engineering students / Haslin Idayu Amaruddin and Siti Hawa Rosli - Amaruddin, Haslin Idayu; Rosli, Siti Hawa (Universiti Teknologi MARA, Pahang, 2022)
Social media like YouTube has been used globally by teachers and educators for open distance learning (ODL) during pandemic COVID19. Most teachers upload lecture videos on YouTube for easy access. The video's duration is generally long up to 15 minutes or more. Creating short video (60 seconds) content is one of the benefits of emerging technology in the digital era. Nowadays, there are a lot of applications available to help social media users to create interactive video content. By creating a short video on Tik Tok or YouTube as an alternative to recorded lecture videos, educators can create an interesting learning environment to enhance students' performance. This study tended to create an overview of how a short video helps Civil Engineering diploma students to remember basic theories in Reinforced Concrete (RC) Design. RC Design course involved a lot of formulas and calculations. A mistake in the theories will cause wrong design solutions. Three groups of students participated in this study. These three groups are under the same lecturer to eliminate the factors that influence the performance of the students based on the lecturer's method of delivery. In this study, students were provided with short videos on the theories of RC Design. A questionnaire was then distributed to students to obtain their perception on the use of short video contents as learning tools. The results show that short videos are reliable tools in delivering a technical course in engineering education.